Preparation of Poly O-Toluidine/Titanium Dioxide by In situ Chemical Oxidation Polymerization and Application for Solar Cell. - Hayder A Hasan; Khalid I Ajeel (collage of education / university of Misan, 2020)
Various treatments on the PEDOT:PSS films were carried out to investigate it's influence on the conductivity, morphology, transmittance and the corresponding impact of the performance of the organic photovoltaic devices based on the PCPDTBT:PCBM and P3HT:PCBM blends. These processing including doping PEDOT:PSS with DMF and ME solvents and exposing these films to the vapor of DMF and ME solvents, separately. A considerable enhancement of the conductivity and transmittance of PEDOT:PSS was observed after doping solvent into the PEDOT;PSS solution followed by solvent treatment through exposing these films to solvents environment. The best organic PV doped devices based on either PCPDTBT:PCBM or based on P3HT:PCBM with power conversion efficiency were 2.93% compared to 1.87% for the pristine  PV devices or 2.79% compared to 1.77%  for the pristine devices, respectively. The conductivity improvement was highly influenced by solvent treatment.